2011
DOI: 10.1371/journal.pcbi.1002058
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Microscopic Motility on the Swimming Behavior of Parasites: Straighter Trypanosomes are More Directional

Abstract: Microorganisms, particularly parasites, have developed sophisticated swimming mechanisms to cope with a varied range of environments. African Trypanosomes, causative agents of fatal illness in humans and animals, use an insect vector (the Tsetse fly) to infect mammals, involving many developmental changes in which cell motility is of prime importance. Our studies reveal that differences in cell body shape are correlated with a diverse range of cell behaviors contributing to the directional motion of the cell. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
60
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(77 citation statements)
references
References 37 publications
16
60
1
Order By: Relevance
“…In Fig. 8(a) we plot the time dependence of ε for our model trypanosome during swimming which is similar to experiments [33]. However, ε(t) varies between 0.7 and 0.85 with an average of about 0.76 which is above the experimental value.…”
Section: Swimming Of the Model African Trypanosomesupporting
confidence: 68%
See 2 more Smart Citations
“…In Fig. 8(a) we plot the time dependence of ε for our model trypanosome during swimming which is similar to experiments [33]. However, ε(t) varies between 0.7 and 0.85 with an average of about 0.76 which is above the experimental value.…”
Section: Swimming Of the Model African Trypanosomesupporting
confidence: 68%
“…Experiments have demonstrated that the end-to-end distance of the cell body of a swimming trypanosome amounts to ca. 60% of its cell body length [33]. We have adjusted the values of the parameters κ s , κ b and κ w such that in the simulations the end-to-end distance is around 76%.…”
Section: African Trypanosomementioning
confidence: 99%
See 1 more Smart Citation
“…Differences in cell body shape are correlated with a diverse range of cell behaviors contributing to the directional motion of the cell. For instance, straighter cells swim more directionally, whereas cells that exhibit little net displacement appear to be more bent (80). Because the flagellum is attached laterally along the length of the cell body, a helical wave of the flagellum necessarily applies a torsional stress to the cell body.…”
Section: Discussionmentioning
confidence: 99%
“…31 Motion is transported or super-diffusive for a > 1, limited or sub-diffusive for a < 1, and freely diffusing or random walk-like for a ¼ 1. 31,32 In order to analyze the 1D-rotational motion of confined RBCs in the image plane in addition to the cell membrane edge fluctuations, the mean-centered Cartesian coordinates of the RBC's contours were first converted into polar coordinates with the radius r at the angle b at equiangular distances of 0.5 . The polar coordinates were then partitioned into a Fourier function, rðb; tÞ ¼ c 0 ðtÞ þ P n q¼1 ½c q ðtÞ Á cos ðq Á b þ / j ðtÞÞ , using multiple trigonometric regression.…”
Section: Analysis Of Diffusive Behavior and Cell Membrane Edge Fluctumentioning
confidence: 99%